Strategi Penguatan Cyber Security Guna Mewujudkan Keamanan Nasional di Era Society 5.0 - Eko Budi; Dwi Wira; Ardian Infantono (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The concept of Society 5.0 is human-centered and technology-based. Where the maindrivers of industry are technology and modern society. In the era of technology and information growing rapidly, it has an impact on all aspects of life. One of them is the security aspect in the form of cyber crime threats. Therefore, cyber security has a vital role to prevent the occurrence of cyber crime. The purpose of this study is to obtain an overview of cyber crime and its challenges in the future, cyber security strategies in Indonesia and strengthening cyber security in Indonesia in order to realize national security in the era of society 5.0. The research method used is a qualitative and descriptive analytical approach with data collection techniques using literature studies from previous studies and other secondary data. The result of this study is that the Covid-19 pandemic is the main topic in cybersecurity trends. Hackers took advantage of public unrest as a loophole to launch various attacks, ranging from phishing to ransomware, the data leak of 91 million users of the online shopping site Tokopedia and the data leak of 1.2 million users of the Bhinneka site. Indonesia has also been affected by global cybersecurity cases such as Coronavirus Ransomware, Covidlock Malware, Border Gateway Protocol hacking, vulnerabilities in Draytek Vigor router products, Remote Code Execution on several versions of Windows operating system products, vulnerabilities in Arbitrary Code Execution on all Google Android operating systems, to exploitation of Solar Winds Orion Platform products. The conclusion is that currently Indonesia is in a state of cyber security emergency and has reached an alarming stage. Cyber security strategies that must be carried out by Indonesia to realize nationalsecurity in the era of society 5.0, are 1) capacity building, 2) Formation of special laws on cyber crimes, 3) Increasing human resources, 4) Domestic stakeholder cooperation and international cooperation cyber security sector to realize national security in society 5.0.